PENGARUH PERSEPSI, MOTIVASI, DAN PENGETAHUAN PRODUK TERHADAP MINAT MENABUNG DI BANK SYARIAH PADA MASYARAKAT KABUPATEN SIDOARJO - Azmiel Habibatul Hazarillah; Norma Rosyidah (Universitas KH. A. Wahab Hasbullah, 2023)
Indonesia’s development Banking is increasing from year to year. Since the enactment of Law Number 10 of 1998 which states the existence of a dual banking system and the 2003 MUI fatwa concerning banking interest rates prohibition, this is a strength for Islamic banks to continue to grow. This very significant Islamic banks development is proof that Islamic banks are getting closer to the community. The people of Sidoarjo Regency themselves have their own interest in saving at Islamic banks, whether it is seen from the products they have, their perception of Islamic banks, or the motivation for the community in Sidoarjo Regency to save in Islamic banks. This study is a quantitative study that analyzes the effect of perception, motivation, and product knowledge on interest in saving in Islamic banks. The sample in this study found 71 respondents, namely the people of Sidoarjo Regency who have become customers at Islamic banks. The data obtained were processed using SPPS 23. The results of this study indicate that partially perception, motivation, and product knowledge affect the interest in saving in Islamic banks. Simultaneously perception, motivation, and product knowledge have a significant effect on interest in saving in Islamic banks Keywords: Perception, Motivation, Product knowledge, Interest in saving